Struktur Komunitas Gastropoda sebagai Bioindikator Pencemaran Air Sungai Gorong Kabupaten Lombok Tengah dalam Upaya Penyusunan Petunjuk Praktikum Ekologi - Hadi, Iwan (Biocaster : Jurnal Kajian Biologi, 2023)
Gastropods are invertebrate animals that have a soft-bodied morphology, mostly shelled, then walk using their stomachs and live only in waters as their habitat. One of the waters used as a habitat for gastropods is the Gorong River. Gorong River is one of the rivers located in Pengadang Village, Praya Tengah District, Central Lombok Regency, which has a fairly high diversity of gastropods. Gastropod diversity can be used as a bioindicator of water pollution. This study aims to determine the species, population, diversity, and abundance of conch (Pilla ampullacea) in the Gorong River, Central Lombok Regency as material for preparing ecological practical instructions. This type of research is descriptive exploratory. Gastropod sampling was carried out at 3 stations using purposive sampling technique. Based on the research results, there were 5 types of gastropods, namely: Melanaides granifera, Pilla ampullacea, Thiara pantherina, Thiara scabra, and Salinator burmana. Dominance index values ​​ranged from 0.154-0.999, diversity index values ​​(Shannon-Wiener) ranged from 0.326-0.807, and the abundance of all snails found in the gorong river in Pengadang Village was 122 snails. Based on the results of the chemical physics parameter assessment at the three stations, which ranged from 270C-330C, current speed 6-30 m/s, depth 9-30 m/s, pH 8.36-8.49, DO 8.03-8.10 mg /L, BOD 5.78-5.00 mg/L, and COD 15.68-15.68 mg/L. The results of the validation of the practicum instructions from the three expert validators were between 68-93 and the student readability test between 60-100 which means very good, so that the preparation of the ecological practicum instructions was declared feasible to use.